Modelling supply chain coordination for performance improvement using analytical network process-based approach. (2018) - Shukla, Rajendra Kumar; Garg, Dixit; Agarwal, Ashish
In order to improve coordination in the supply chain, the selection of a supply chain coordination mechanism plays an important role. Due to the multi-dimensional nature of a supply chain problem, the selection of the right supply chain coordination mechanisms (SCCMs) in a given situation remains a difficult and most challenging task for supply chain managers. In this paper, an attempt has been made first to explore various issues pertaining to the selection and implementation of SCCMs and finally to create an analytical network process (ANP) based framework to help supply chain managers to take appropriate steps in the selection of SCCMs in a given situation. The framework presented in this paper summarises the role of market responsiveness, process integration, risk, requirement and flexibility for supply chain performance. The paper explores the relationship among cost, flexibility, quality, service level and lead time to prioritise coordination mechanisms of supply chain for Indian manufacturing companies. The paper concludes with the justification of the framework, which analyses and prioritises the alternatives using ANP to improve coordination in supply chain.